Citizens' electronic participation: a systematic review of their challenges and how to overcome them. (10th July 2019) - Oliveira, Carlos; Garcia, Ana C.B.
The evolution of the internet and the popularity of the social media have brought new possibilities for citizens' participation into government decision-making. Laws, in democratic countries, have enforced government's data and process transparency. Nevertheless, the e-government research has demonstrated that citizen's participation is still very low. This paper presents a systematic literature review of e-participation research addressing three questions: 1) what are the reasons for the low citizens' participation?; 2) what is the role of the government in e-participation?; 3) what are the current approaches to promote e-participation? Although participation is a right for which the citizens should be fighting for, they have been neglecting to act. Researchers have indicated the government still plays a central role since information and opportunities flow through the government-controlled technological platforms. Nonetheless, there is hope, to initiate a virtuous cycle in which citizens control and expand popular participation, leading to a greater demand for government action.